A strong and biodegradable wood particles-based bioplastic modified by synergistically dynamic cross-linking with tannic acid and Fe3+. (December 2022) - Zhou, Zhezhe; Liu, Tao; Zhou, Wenguang; Chen, Hui; Bian, Yanyan; Gong, Shanshan; Shi, Sheldon Q.; Li, Jianzhang
Abstract: The widespread use of petrochemical plastics has caused surging environmental problems and health hazard. Fabrication of biodegradable, eco-friendly and high-performance bioplastic with a facile and efficient way to replace petrochemical materials remains an enormous challenge. As low-cost and abundant sustainable materials, wood particles have the advantages of good processing performance and have been widely studied recently. Herein, a new high-performance sustainable bioplastic was constructed with delignified wood particles (DWP) matrix and enhanced by tannic acid (TA) crosslinked Fe 3+ through hot-pressing process. The synergy of dynamic hydrogen bonds and coordination bonds endowed the resultant DWP-based bioplastic with a high tensile strength of 57.5 ± 3.17 MPa that surpassed those of most bioplastics and satisfactory water resistance. Moreover, the resulting film remained more than 94% mechanical properties after staying in harsh conditions for a long time, displaying excellent stability. Furthermore, the DWP/TA/Fe 3+ film also demonstrated unique transparency (an average transmittance of 46.74%), decent antioxidant capacity and outstanding biodegradability. In addition, a laminated composite from the DWP-based films and PVA adhesive showed an excellent tensile strength of 70.42 ± 4.52 MPa, higher than some natural woods, which was helpful to expand the industrial application of DWP-based bioplastic. This approach provides a promising pathway for developing strong and sustainable bioplastics with low-cost and abundant biomass sources, and help the development of high-performance bioplastics in the field of disposable tableware, green films and packing materials. Graphical abstract: A high-performance, sustainable and transparent film is constructed from delignified wood particles, tannic acid and Fe 3+ by the synergy of dynamic hydrogen bonds and TA-Fe 3+ coordination bonds, which exhibits attractive close loop cycle and can be assembled into bulk laminated composite as well. Image 1 Highlights: A DWP-based bioplastic is fabricated via dynamic cross-inking with TA and Fe 3+ . The synergy of hydrogen and coordination bonds gives DWP-based film excellent properties. The high-performance film shows glorious biodegradability, antioxidant capacity and stability. A high-performance laminated bulk is obtained by laminating DWP/TA/Fe 3+ film and PVA.